Mathematics courseware for dyscalculia students (MCDYs) / Muhamad Shazrie Suhaidi Noordin ... [et al.] - Suhaidi Noordin, Muhamad Shazrie; Mohd Bahrin, Ummu Fatihah; Hamzah, Siti Salbiah; Sa'dan, Siti 'Aisyah (2020)
MCDys is a courseware created as a learning tool for students with dyscalculia. The syllabus is developed based on the Linus module that is provided by the Kementerian Pendidikan Malaysia (KPM). Dyscalculia is a term used for learners that have a disability in learning mathematics. In developing this courseware, ADDIE model is used. ADDIE is a framework that many instructional designers and developers use to develop the courses. There are five stages in ADDIE Model which are analysis, design, development, implementation, and evaluation. To design the interface, Schneiderman's eight golden rules of interface design is used. Schneiderman's eight golden rules include striving for consistency, enabling frequent users to use shortcuts, offering informative feedback, designing dialogue to yield closure, offering simple error handling, permitting easy reversal of actions, supporting internal locus of control and reducing short-term memory load. The content of the courseware uses interactive approaches such as video, animation, and quizzes, and game-based activities to encourage users' understanding and grab their attention. User evaluation and expert evaluation were conducted to test the effectiveness and acceptance of the interface, usability, activity, navigation, multimedia, sound, image, text, animation, and video. The results show that the courseware has the highest score for usability score with a mean of 4.6(SD=0.55). For future enhancement, more animation will be explored to suit the dyscalculia students' learning.